Pengaruh Modifikasi Lift Camshaft dengan Bahan Bakar Pertamax terhadap Torsi dan Daya Mesin Motor 125 cc - Husen Khalwani; Sigit Mujiarto; Trisma Jaya Saputra (Pusat Riset dan Inovasi Nasional, 2025)
In this modern era, transportation is something that is needed by the general public, especially motorized vehicles, as evidenced by the presence of various new motorized vehicle products. However, the use of motorbikes that have been used daily for more than 5 years will experience a significant decrease in performance, this makes motorcycle owners want to improve the performance of the motorbikes they have. One step that can be taken to improve the performance of a motorcycle engine is to optimize the performance of the camshaft, so motorcycle owners do not need to change the cubic centimeter (cc) of their motorcycle but can optimize engine performance. In this study, the addition of camshaft lift variations of 1.5 mm using experimental methods to find the results of the effect of modifying the camshaft lift which will be adjusted to the engine capacity. The results of this study show an increase in torque and power which is quite significant with the highest torque results achieved on the modified camshaft addition of 1.5 mm lift of 8.6 Nm at 8000 rpm and power of 8.5 hp at 8000 rpm, this is due to the higher suction valve opening the greater the volume of air and fuel mixture entering the combustion chamber, resulting in an increase in torque and power.